Positron emission tomography (PET) radiopharmaceuticals in multiple myeloma - Sachpekidis, Christos; Goldschmidt, Hartmut; Dimitrakopoulou-Strauss, Antonia (Molecules, 2020)
Multiple myeloma (MM) is a plasma cell disorder, characterized by clonal proliferation of malignant plasma cells in the bone marrow. Bone disease is the most frequent feature and an end-organ defining indicator of MM. In this context, imaging plays a pivotal role in the management of the malignancy. For several decades whole-body X-ray survey (WBXR) has been applied for the diagnosis and staging of bone disease in MM. However, the serious drawbacks of WBXR have led to its gradual replacement from novel imaging modalities, such as computed tomography (CT), magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT). PET/CT, with the tracer F-18-fluorodeoxyglucose (F-18-FDG), is now considered a powerful diagnostic tool for the detection of medullary and extramedullary disease at the time of diagnosis, a reliable predictor of survival as well as the most robust modality for treatment response evaluation in MM. On the other hand, F-18-FDG carries its own limitations as a radiopharmaceutical, including a rather poor sensitivity for the detection of diffuse bone marrow infiltration, a relatively low specificity, and the lack of widely applied, established criteria for image interpretation. This has led to the development of several alternative PET tracers, some of which with promising results regarding MM detection. The aim of this review article is to outline the major applications of PET/CT with different radiopharmaceuticals in the clinical practice of MM.
Published: 29 December 2019
Gesehen am 30.03.2020